Analisis Sistem Informasi Order dan Tracking Barang Menggunakan Metode Prototyping pada CV. Untung Maju Bersama - Rian Permatasari; Fabriyan Fandi Dwi Imaniawan; Hidayat Muhammad Nur (STEKOM PRESS, 2022)
Entering an increasingly advanced era, the role of information technology is very important in various sectors. Currently, many business people have used information technology as a system in an agency or company. CV. Untung Maju Bersama is a company engaged in the sale of snacks and basic necessities. In its journey, the system used is still using a manual system. To maximize the sales system, therefore an analysis of the sales system design was made using the prototyping method to help improve the existing system. The system used on this website has three users, namely admin, sales, and delivery who have different access rights and have different tasks according to their respective job descriptions. In the analysis of this information system design, a prototyping method is used where the design made must be in accordance with the system to be built. Several features will be added in this proposed design system which did not exist in the previous system, namely the addition of an item tracking feature. This feature allows customers to see how far their orders have been processed. It is hoped that the design of this system can help CV. Untung Maju Bersama in maximizing sales and data management. Keywords: information systems, order systems, tracking systems, prototyping